(untitled) (Research, Society and Development, 2020)
Objective: to assess neonatal jaundice mortality in Brazil, Northeast and Piauí. Methodology: this is a retrospective epidemiological study, with a quantitative and descriptive design. Secondary data from the Mortality Monitoring Panel ICD-10 of the Ministry of Health of Brazil were used. The study included the series of deaths of children under 1 year of age due to neonatal jaundice and kernicterus, between the years 2010 and 2019, in Brazil, in the Northeast Region and in the State of Piauí. The Microsoft Office Excel 2019 program was used for simple descriptive analysis. Results: in the last 10 years, 1,008 deaths from neonatal jaundice occurred in Brazil. It was observed that mortality was more prevalent in males and in brown color/race. The specific causes of jaundice with higher mortality in Brazil and the Northeast were infection, premature birth and isoimmunization, respectively. In Piauí, the main cause was isoimmunization, followed by infection and premature birth. Conclusion: mortality from neonatal jaundice showed a downward trend in Brazil and the Northeast, while in Piauí it showed a small and stable annual average of cases. The comparison of the epidemiological situation of mortality due to jaundice between Brazil, the Northeast Region and the State of Piauí provides subsidies for the implementation of adequate prevention and control actions.